Pengaruh Diskon Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Maranatha Store - Yonathan Hervan Valentino; Cen Lu (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
The purpose of this study is to determine whether customer satisfaction at Maranatha Store a retail outlet serving university students, lecturers, and staff is influenced by discounts and service quality. The study was conducted by distributing questionnaires to 126 individuals who had previously shopped at the store. The analysis results indicate that discounts and service quality, when considered together, have a significant impact on customer satisfaction. These findings highlight the importance of continuously improving service quality to provide customers with a satisfying shopping experience